SUSTAINABLE DEVELOPMENT AND INTERNATIONAL STANDARDS OF FINANCIAL REPORTING - Eshkuvatova Mukhlisa Avaz kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the era of globalization and increased environmental awareness, the concept of sustainable development has become a core focus for policymakers, businesses, and investors alike. At the same time, the role of financial reporting has evolved beyond the presentation of financial health to encompass transparency in environmental, social, and governance (ESG) matters. This article explores the intersection of sustainable development and International Financial Reporting Standards (IFRS), evaluating how global financial reporting frameworks contribute to the achievement of sustainability goals.